Evaluation of flamelet-based combustion models for the use in a flameless burner under different operating conditions. (25th January 2021) - Mayrhofer, Markus; Koller, Michael; Seemann, Peter; Prieler, Rene; Hochenauer, Christoph
Highlights: Experimental and numerical investigation of a flameless burner at design and off-design operations. Evaluation of different flamelet-based models via industrial test results. Comparison of different reaction mechanisms for flameless combustion application. Off-design behaviour of a flameless burner and NOx formation. Abstract: The thermal input of a flameless burner is commonly realized by its switch on-time at a unique, optimized design point. This typical on–off regulation approach may provide temporal-inhomogeneous temperature distributions in continuous operating furnaces. An alternative way of regulation is a modulated controlled flameless burner, which deals with off-design points and reaches so a more temporal-homogeneous temperature distribution. Influences on the temperature field of the flameless reaction zone, caused by the off-design operation are investigated in this paper. This is done by experimental investigations with an aspirated thermocouple and with numerical simulations, using several flamelet-based combustion models. Additionally, Nitrogen oxide emissions were measured for each design point, which starts from 165 kW at nominal power to lower limit of 60 kW. The results suggest, that the non-premixed flamelet model is suitable for the application of flameless combustion in design and off-design. Furthermore, local temperature peaks in the flameless reactions zone increase (from about 1450 to 1530 °C) and the NOx emissions increase (from about 32 to 88 ppm) by decreasing the thermal input of the flameless burner at constant furnace temperatures.